Acitretin: Monotherapy or Combined Therapy for Hidradenitis Suppurativa?. Issue 1 (January 2017) - Tan, Marcus G.; Shear, Neil H.; Walsh, Scott; Alhusayen, Raed
Background: Hidradenitis suppurativa (HS) is a chronic, recurrent inflammatory disease of the pilosebaceous follicle that severely affects patients' quality of life and can be challenging for clinicians to manage. A few case series have reported on the efficacy of acitretin monotherapy in the treatment of intractable HS. Objective: To assess the efficacy of acitretin for the treatment of intractable HS. Methods: A retrospective review was conducted involving all patients with HS who received acitretin between January 2011 and January 2015 in a tertiary academic medical center. All patients with HS who received acitretin, either as a monotherapy or as an adjuvant to other systemic medications, were included, and clinical response was assessed using the physician global scale. Results: Fourteen patients with HS (mean age 48 years [range 32-64 years]; 9 [64%] were men) received acitretin. Most patients (86%) had Hurley stage II or III disease. All patients had failed other standard systemic medications prior to initiating acitretin. Six patients (43%) received acitretin monotherapy, and 8 patients (57%) received acitretin as an adjuvant to other standard systemic medications. None of the patients who received acitretin monotherapy exhibited clinical improvements. Clinical improvements were observed in 7 of the 8 (87.5%) patients who received acitretin as an adjuvant to other systemic medications, with 3 patients (37.5%) exhibiting partial response and 4 patients (50%) exhibiting good response. Conclusions and Relevance: Acitretin monotherapy was ineffective for the treatment of intractable HS. Acitretin may be effective when used as an adjuvant to other systemic medications.